2018
DOI: 10.1186/s13046-018-0887-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between epithelial-to-mesenchymal transition and the inflammatory microenvironment of hepatocellular carcinoma

Abstract: Epithelial-to-mesenchymal transition (EMT) is a complex process involving multiple genes, steps and stages. It refers to the disruption of tight intercellular junctions among epithelial cells under specific conditions, resulting in loss of the original polarity, order and consistency of the cells. Following EMT, the cells show interstitial cell characteristics with the capacity for adhesion and migration, while apoptosis is inhibited. This process is critically involved in embryogenesis, wound-healing, tumor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 119 publications
(110 reference statements)
1
80
0
Order By: Relevance
“…In recent studies, increasing evidence demonstrated that lncRNA plays a crucial biological role in the initiation, progression, metastasis, and recurrence of tumor . Moreover, lncRNAs could also serve as the promising biomarkers for prognosis and diagnosis in various tumors . Increasing research has showed that dysregulation of lncRNAs were correlated with the carcinogenesis of CCA, as well as decreasing the survival rate of patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, increasing evidence demonstrated that lncRNA plays a crucial biological role in the initiation, progression, metastasis, and recurrence of tumor . Moreover, lncRNAs could also serve as the promising biomarkers for prognosis and diagnosis in various tumors . Increasing research has showed that dysregulation of lncRNAs were correlated with the carcinogenesis of CCA, as well as decreasing the survival rate of patients .…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Moreover, lncRNAs could also serve as the promising biomarkers for prognosis and diagnosis in various tumors. [24][25][26][27] Increasing research has showed that | 18999 dysregulation of lncRNAs were correlated with the carcinogenesis of CCA, as well as decreasing the survival rate of patients. 28,29 Therefore, it is necessary to identify potential lncRNAs acting as promising prognostic biomarkers, which could function as a potential therapeutic target for patients with CCA.…”
Section: Discussionmentioning
confidence: 99%
“…For this work, we implemented Pathrider [9] in order to extract a subgraph from the KEGG generic human signaling network (obtained in the previous section). Given a list of genes and a network, Pathrider will keep only the signaling pathways of the network regulating the list of genes, that is, the upstream paths of the nodes in the network that represent these genes.…”
Section: Extracting Up-stream Signaling Pathwaysmentioning
confidence: 99%
“…Pathrider will also filter out the biomolecules [8] File hsa-2345-symb-nomulti-split-func-sign.sif at https://github.com/LokmaneChebouba/key-pipe/ tree/master/example. [9] Available at: https://github.com/arnaudporet/pathrider in the graph (genes, proteins or protein complexes) that appear in a list of excluded genes, which in practice refer to genes whose expression is undetectable. This tool is included in the automatic pipeline we propose in this work (see Section 2.1).…”
Section: Extracting Up-stream Signaling Pathwaysmentioning
confidence: 99%
“…Tumor metastasis displays a number of unique characteristics, including migration and invasion; however, the mechanisms of tumor migration and invasion have not been fully determined. Recently, it was identified that epithelial-mesenchymal transition (eMT), which is the transformation of epithelial cells into mesenchymal cells, can significantly enhance the motility of cancer cells (8).…”
Section: Introductionmentioning
confidence: 99%